2016
DOI: 10.4314/afrrev.v10i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Relationship between Crude Oil Price, Exchange Rate and Stock Market Performance in Nigeria

Abstract: This study employed a multivariate Vector Error Correction Model (VECM) that uses the Granger causality test and generalized variance decomposition analysis to study the relationship between crude oil prices, exchange rate and stock market performance in Nigeria from January 1995 to December 2014. As expected from an oil exporting country, a short-run positive relationship is observed between the Nigerian stock market and crude oil prices and the direction is from crude oil prices to the Nigerian stock market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…The conditional volatility of stock market price log return was found to be stable and predictable while that of crude oil price log return was found to be unstable and unpredictable although a dependable and dynamic relationship between crude oil prices and stock market prices was found to exist. The cointegration test result of this study agrees with the findings of [17,18,19,20] among others.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The conditional volatility of stock market price log return was found to be stable and predictable while that of crude oil price log return was found to be unstable and unpredictable although a dependable and dynamic relationship between crude oil prices and stock market prices was found to exist. The cointegration test result of this study agrees with the findings of [17,18,19,20] among others.…”
Section: Resultssupporting
confidence: 92%
“…Results showed a significant link between oil prices and stock market performance in Nigeria. Iheanacho [19] conducted a study that employed a multivariate Vector Error Correction Model (VECM) which used Granger causality test and generalized variance decomposition analysis to study the relationship between crude oil prices, exchange rate and stock market performance in Nigeria from January 1995 to December 2014. The study found a short-run positive relationship between crude oil prices and the Nigerian stock market with the direction of causality running from crude oil prices to the Nigerian stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various studies on the effect of crude oil price fluctuation on the stock market in Nigeria show mixed results. For instance, Omisakin et al (2009), Mordi et al (2010), Abbas and Terfa (2010), Adebiyi et al This Journal is licensed under a Creative Commons Attribution 4.0 International License (2010), Akomolafe and Danladi (2014), Akinlo (2014), Iheanacho (2016), Lawal et al (2018), Soyemi et al (2017), Ojikutu et al (2017), Obi et al (2018) observe a positive effect of oil price shock on the stock price. On the contrary, studies like Adaramola (2012) and Effiong (2014) reported an inverse correlation between the price of oil movements and returns from stocks.…”
Section: Introductionmentioning
confidence: 99%
“…(2015) , Uwubanmwen and Omorokunwa (2015) , Lawal et al. (2016) , Iheanacho (2016) , Mroua and Trabelsi (2019) , and Manasseh et al. (2019) .…”
Section: Empirical Literaturementioning
confidence: 99%